Plastichnost' kak dvigatel'no-koordinatsionnoe kachestvo - Nazarenko, L. D. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The reasoning of plasticity as a variety of movable-coordinative feature is given in the article. The essence of the structure, specific and non-specific manifestation is revealed. The importance and necessity of development of this feature is shown.